Minat Mengaji dan Membayar Zakat Maal pada Masyarakat pedukuhan Tanjungsari RT.03, Sukoharjo, Ngaglik, Sleman - Salmahaminati Salmahaminati (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
Tanjungsari village which is part of Sukoharjo village, Ngaglik sub-district, Sukoharjo. The population is in the productive age range (15-44 years). in Tanjungsari village, Sleman, Yogyakarta, it is estimated that they are still unable to read and write Arabic. The extension activities that have been carried out are in the form of appeals and formation of groups to increase interest in the Qur'an and practice zakat maal in the RT.03 community, in Tanjungsari village, Sukoharjo, Sleman, Yogyakarta through the media of learning tajwid and analysis through observation and surveys. These activities can foster awareness of the importance of reading and writing understanding of the reading of the Qur'an and foster interest in reading and writing Arabic letters for a person and the partner community can practice zakat maal and alms.